Neurophysiologic assessment of small fibre damage in chemotherapy-induced peripheral neuropathy - İŞAK, BARIŞ (ELSEVIER IRELAND LTD, 2021)
Objective: In patients with chemotherapy-induced peripheral neuropathy (CIPN), demonstration of small fibre (SF) damage is important to understand chronic late effects. Methods: Thirty patients having complaints compatible with possible CIPN following treatment with oxaliplatin or docetaxel were compared with 27 healthy subjects. All subjects were evaluated with quantitative sensory testing (QST) assessing SF function and laser evoked potentials (LEP). In addition, SF-damage was assessed using cutaneous silent periods evoked with electrical (El-CSP) and laser (Ls-CSP) stimuli. Results: For LEP, N2P2 amplitudes were significantly smaller in patients than controls in both upper (P = 0.007) and lower extremities (P = 0.002), and the N1 amplitude in upper extremities of patients were significantly smaller than in controls (P = 0.001). SF-QST, LEP, Ls-CSP, and El-CSP were abnormal in 10 (33.3%), 16 (53.3%), 19 (63.3%), and 24 (80%) of CIPN patients, respectively. Conclusions: In patients with possible CIPN, El-CSP and Ls-CSP were more often abnormal than LEP and QST. This is probably because El-CSP and Ls-CSP inform mainly about peripheral nociceptive fibres, while LEP and QST inform about peripheral and central nociceptive pathways together. Significance: LEP and QST are established methods to detect SF-damage. El- and Ls-CSP might help clinicians in diagnosing SF-damage. (C) 2021 International Federation of Clinical Neurophysiology. Published by Elsevier B.V. All rights reserved.
Keywords: Chemotherapy; Small fibre; Laser; Quantitative sensory testing; Cutaneous silent period; CUTANEOUS SILENT PERIOD; LASER EVOKED-POTENTIALS; SKIN TEMPERATURE; INFRARED-LASER; HAIRY SKIN; PAIN; STIMULATION; AFFERENTS; ABNORMALITIES; SENSITIZATION